2013
DOI: 10.1007/s00775-013-1033-1
|View full text |Cite
|
Sign up to set email alerts
|

Human anamorsin binds [2Fe–2S] clusters with unique electronic properties

Abstract: The eukaryotic anamorsin protein family, which has recently been proposed to be part of an electron transfer chain functioning in the early steps of cytosolic iron-sulfur (Fe/S) protein biogenesis, is characterized by a largely unstructured domain (CIAPIN1) containing two conserved cysteine-rich motifs (CX 8 CX 2 CXC and CX 2 CX 7 CX 2 C) whose Fe/S binding properties and electronic structures are not well defined. Here, we found that (1) each motif in human anamorsin is able to bind independently a [2Fe-2S] c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 50 publications
(73 reference statements)
6
56
0
Order By: Relevance
“…Ciapin1 is an early acting factor in the maturation of newly synthesized [4Fe-4S] clusters in the CIA pathway (43,44). Ciapin1 itself contains two bound Fe-S clusters that are thought to function in the transfer of reducing equivalents from the flavoprotein Ndor1 to downstream components of the CIA (45,46). We confirmed the presence of the Glrx3⅐Ciapin1 complex in cells by detecting endogenous Ciapin1 in Glrx3-FLAG immunoprecipitates (Fig.…”
Section: Glrx3 Forms Homodimers Independent Of Bound Fe-s Clusters-prsupporting
confidence: 56%
“…Ciapin1 is an early acting factor in the maturation of newly synthesized [4Fe-4S] clusters in the CIA pathway (43,44). Ciapin1 itself contains two bound Fe-S clusters that are thought to function in the transfer of reducing equivalents from the flavoprotein Ndor1 to downstream components of the CIA (45,46). We confirmed the presence of the Glrx3⅐Ciapin1 complex in cells by detecting endogenous Ciapin1 in Glrx3-FLAG immunoprecipitates (Fig.…”
Section: Glrx3 Forms Homodimers Independent Of Bound Fe-s Clusters-prsupporting
confidence: 56%
“…We previously reported that the WT Dre2 protein contains one [2Fe2S] cluster and one [4Fe4S] cluster by EPR analysis (11). Although this finding has been supported by more recent studies (1214), some other studies on anamorsin, the hDre2 homolog, claimed that these two cysteine motifs independently bind a [2Fe2S] cluster in a mutually exclusive manner (19). To resolve the discrepancy, we decided to perform site-directed mutagenesis by mutating each of the cysteine residues to alanine, specifically aiming to disrupt one cluster while not affecting the other.…”
Section: Resultsmentioning
confidence: 61%
“…The physiological relevance of the interface of hGRX5 interacting with hISCA1 and hISCA2 was verified by investigating the interaction of hGRX5 with the nonphysiological partner anamorsin, which is a human [2Fe-2S] protein involved in the cytosolic iron-sulfur protein assembly machinery (25,31,32). Specifically, when titrating 15 N-labeled apo hGRX5 with unlabeled [2Fe-2S]-anamorsin no significant chemical shift changes are observed (Fig.…”
Section: It Results That (I) the [2fe-2s]mentioning
confidence: 99%